A new technique for performing interstitial implants for gynecologic malignancies using transvaginal ultrasound guidance - Yan, Xiao-Jing; Yang, Yi; Chen, Xi; Wang, Shi-Guang; Niu, Shu-Huai; Niu, Hui-Xian; Liu, Hong (Frontiers in Oncology, 2022)
Objectives This study concerns a new technique that aims to achieve precise interstitial brachytherapy of pelvic recurrent tumors under transvaginal ultrasound (US) guidance, enhance the conformity index of the brachytherapy (BT), and improve the curative effect of radiotherapy for gynecological oncology patients with pelvic relapse. Methods A real-time transvaginal US-guided interstitial implant device was developed to assist in implant BT. Prior to implant brachytherapy, the size and location of the tumor in the pelvis and the interrelationship with adjacent organs were first assessed with intracavitary ultrasound. The transvaginal US-guided interstitial implant device was then placed on the endoluminal ultrasound probe, the probe was oriented intravaginally to determine a safe needle path, the implant needle was placed into the needle passage of the device, and the implant needle was inserted into the tumor tissue in the direction guided by the ultrasound puncture guide line. After the implant needle was placed in place, the cover of the transvaginal US-guided interstitial implant device was opened perpendicular to the ultrasound probe, and the needle was separated from the ultrasound probe smoothly, and then the cover was re-covered for subsequent implantation. Results In this study, 56 patients who underwent real-time transvaginal ultrasound-guided implantation for gynecologic oncology were enrolled, and insertion of 736 implant needles was completed. Among them, 13 patients had recurrent pelvic tumors after cervical cancer surgery and 6 patients had recurrent pelvic tumors after endometrial cancer surgery. Thirty-two patients who underwent radical radiation therapy for cervical cancer did not have adequate regression of parametrial invaded tissue after completion of standard EBRT treatment; and 5 patients had recurrent tumors in the radiation field after previous standard course of pelvic radiotherapy. The accuracy of the implant therapy was improved. The radiotherapy dose for recurrent pelvic masses was successfully increased, and the cumulative dose of external irradiation combined with BT was augmented to 80–100 Gy. The use of a new device for transvaginal implant for recurrent masses located in the lateral wall of the pelvic cavity was successful. Conclusion This intravascular US-guided interstitial implant device can realize interstitial implant with the shortest path under transvaginal US guidance. With convenient operation, high precision, and good security, the device not only improves the accuracy of implant therapy, but it also reduces the risks of anesthesia and organ injury, so it is suitable for widespread promotion and use.